The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.13187/es.2015.12.76
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trade Openness, Exchange Rate, and Oil Price on the Exports in Syria

Abstract: This study attempts to test the effect of trade openness, exchange rate and oil price on the exports in Syria over the period . The cointegration test indicates that exports are positively related to trade openness and oil price, but negatively related to exchange rate. Exchange rate has the biggest effect on the exports. The Granger causality test indicates bidirectional causality relationships between trade openness, exchange rate, oil price and exports in the short and long run. The study result indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…The result is in line with Hoque and Yusop, Z. [5], Mohsen [10], Epaphra [7], and Mohsen et al [11] (2017). In conclusion, GDP per capita and real exchange rate both impact road vehicle exports.…”
Section: The Cointegration Testsupporting
confidence: 91%
See 1 more Smart Citation
“…The result is in line with Hoque and Yusop, Z. [5], Mohsen [10], Epaphra [7], and Mohsen et al [11] (2017). In conclusion, GDP per capita and real exchange rate both impact road vehicle exports.…”
Section: The Cointegration Testsupporting
confidence: 91%
“…The results revealed that the exchange rate, GDP per capita, and trade liberalization had a positive effect on export performance. Similarly, Mohsen [10], investigated the impact of oil prices, trade openness, and exchange rate on the Syria's exports for the period of 1970-2010. The results from the cointegration test revealed that trade openness and oil prices were positively related to Syrian exports, but the exchange rate showed a negative relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Palumbo et al (2010), based on overall assessment, they can be classified as having negative, positive or no influence on the economic growth. One group of researchers has shown evidence positive influence of population in economic development (Ali et al, 2013;Azam et al, 2020;Guga et al, 2015;Mamun et al, 2017;Mohsen & Chua, 2015;Musa, 2015;Nyoni & Bonga, 2017;Sebikabu et al, 2020;Sethy & Sahoo, 2015;Thuku et al, 2013). Another group of researchers argues that population has a negative link with economic growth (Abdullah et al, 2015;Ahmed, 2018;Ahmed & Ahmad, 2016;Faruk, 2019;Gatsi & Appiah, 2020;Ogbuabor et al, 2018;Onime, 2019;Sibt e Ali et al, 2018;Ugwuanyi, 2018;Wako, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have also provided insights into where no significant statistical relationship could be found between population growth and economic development (Jarjusey & Palamuleni, 2017;Karim & Amin, 2018;Sarker et al, 2016). There is also a group researchers who presented that population has bi-directional causality with the economic growth (Mohsen & Chua, 2015;Thuku et al, 2013;Wako, 2012). Furthermore, there was also a group of researchers that has shown that population growth showing unidirectional causality exist among population and economic growth (Ahmed, 2018;Anudjo, 2015;Faruk, 2019;Musa, 2015;Rahman et al, 2017;Sarker et al, 2016;Ugwuanyi, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation